The effect of weights on the return and risk of stock portfolios (Applied Study in the Amman Stock Exchange) (Journal of Hama University, 2019)
The aim of this study is to show the effect of the weights of stocks involved in the portfolio composition in its return and risk by applying to a sample of shares of companies listed on the Amman Stock Exchange during the period 2011-2016. To achieve this objective, Start with a portfolio of only two shares, and then increase the number of shares by one share at a time, equivalent weights were adopted for the shares of the first group, while the use was based on use  Quadratic programming model in the determination of the weights of the shares of the second group, so that the change in the yield and risk of the equity portfolios of equal weights is compared with the change in the yield and risk of the constituent portfolio using Quadratic programming model Thus showing the effect of weights on both the return and risk of stock portfolios. The research found that there is an impact of the weights of the components of the portfolio in their return and risk, This effect varies depending on the method used to determine these weights, The investor in the Amman Stock Exchange has recommended the adoption of the quadratic programming model As a basis and a decision-making approach for identifying the components of the investment portfolio, due to the role of the model in achieving the investor's goals in maximizing return and reducing risk, in addition to the need to benefit investors in other financial markets from the benefits of applying this model, especially investor in the Damascus Stock Exchange.